2015
DOI: 10.12693/aphyspola.128.b-132
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Shielding Properties of Spark Plasma Sintered Boron Carbide-Aluminium Composites

Abstract: In this study gamma and neutron attenuation properties of boron carbide-aluminium (B4C-Al) composites were investigated. B4C-Al composites were produced by spark plasma sintering method. Aluminum percentages in the B4C-Al composites were 0%, 10%, 15%, and 20% by volume. The composite materials were performed against gamma and neutron sources. Cs-137 and Co-60 gamma radioisotopes were used as gamma sources and Pu-Be neutron howitzer was used for neutron source. Theoretical mass attenuation coefficients were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 7 publications
(8 reference statements)
3
8
1
Order By: Relevance
“…Furthermore, they are similar to the values reported for B4C Al metal matrix composites [7] at a gamma energy level of 661.7 keV. However, the linear attenuation coefficients of Al2O3.TiO2;mm and Al2O3.TiO2;nm are lower than those of Al-4% Cu/B4C metal matrix composites [6] and TiB2-reinforced B4C-SiC [10] The best HVL value of 3.57 cm obtained in this study is better than the results of [9], but significantly less than the values reported for some stainless and boron steels [8].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, they are similar to the values reported for B4C Al metal matrix composites [7] at a gamma energy level of 661.7 keV. However, the linear attenuation coefficients of Al2O3.TiO2;mm and Al2O3.TiO2;nm are lower than those of Al-4% Cu/B4C metal matrix composites [6] and TiB2-reinforced B4C-SiC [10] The best HVL value of 3.57 cm obtained in this study is better than the results of [9], but significantly less than the values reported for some stainless and boron steels [8].…”
Section: Resultssupporting
confidence: 86%
“…The linear attenuation coefficients of Al2O3;mm and Al2O3;nm are similar to those of TiB2-reinforced B4C-silicon carbide composites [5] and spark plasmasintered B4C-Al [9]; however, they are higher than the values reported for h-BN and h-BN-TİB2 composites [4] and lower than those of Al-4% Cu/B4C metal matrix composites [6], B4C Al metal matrix composites [7], and some stainless and BSs steels [8] at 661.7 keV. At gamma energies of 1173.2 and 1332.5 keV, Al2O3;mm and Al2O3;nm samples have lower linear attenuation coefficients than Al-4% Cu/B4C metal matrix composites [6] and TiB2-reinforced B4C-SiC [10].…”
Section: Resultssupporting
confidence: 56%
“…After the irradiation, all TLDs were read out on the Harshaw 2000A TLD reader. The resulting data provided a profile of relative sensitivities among TLDs in this single holder [9][10][11][12][13]. Actually before the dose assessment some study which shows the TLDS' sensitivities should be done and for this purpose the calibration factor for dosimeters and readers was obtained according to Cr-51.…”
Section: Methodsmentioning
confidence: 99%
“…Composite materials are used in a wide range of applications [6][7][8][9][10][11][12][13]. A lot of work has been done towards producing and evaluating the electrical performance of contact materials [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%